The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.1021/ja300797g
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Light-Driven Water Oxidation Catalyst

Abstract: Two mononuclear Ru(II) complexes, [Ru(ttbt)(pynap)(I)]I and [Ru(tpy)(Mepy)(2)(I)]I (tpy = 2,2';6,2"-terpyridine; ttbt = 4,4',4"-tri-tert-butyltpy; pynap = 2-(pyrid-2'-yl)-1,8-naphthyridine; and Mepy = 4-methylpyridine), are effective catalysts for the oxidation of water. This oxidation can be driven by a blue (λ(max) = 472 nm) LED light source using [Ru(bpy)(3)]Cl(2) (bpy = 2,2'-bipyridine) as the photosensitizer. Sodium persulfate acts as a sacrificial electron acceptor to oxidize the photosensitizer that in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
125
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(127 citation statements)
references
References 47 publications
2
125
0
Order By: Relevance
“…S14). These transitions were nearly identical to those observed with NOPF 6 , but also include the overlapping absorption spectra of [Ru(bpy) 3 [36] and the consequent O 2 evolution was monitored. O 2 evolution was observed after an initial delay time of ~2 min of irradiation (Fig.…”
Section: Photochemical Water Oxidation With [Mn 2 L] N+supporting
confidence: 69%
See 1 more Smart Citation
“…S14). These transitions were nearly identical to those observed with NOPF 6 , but also include the overlapping absorption spectra of [Ru(bpy) 3 [36] and the consequent O 2 evolution was monitored. O 2 evolution was observed after an initial delay time of ~2 min of irradiation (Fig.…”
Section: Photochemical Water Oxidation With [Mn 2 L] N+supporting
confidence: 69%
“…The induction period is due in part to the low light intensity of the LEDs in this setup and the small driving force of [Ru(bpy) 3 ] 3+ toward the higher oxidation states of [Mn 2 L] n+ required for water oxidation. [36,41] O 2 evolution from the system was observed for several concentration ranges of [Mn II 2 L] 2+ and proceeded over 30 min. A series of control experiments confirmed all four components (i.e.…”
Section: Photochemical Water Oxidation With [Mn 2 L] N+mentioning
confidence: 99%
“…For these types of complexes, fast intramolecular electron transfer (ET) from to the active catalyst (Ru C ) oxidized PS (Ru P ) can occur through the bridging ligand [11], so the system is considerably more effective than an isolated three-component system using essentially the same PS and catalyst components [21,37]. Sun and co-workers have reported a trinuclear supramolecular complex 26 [11] .Thummel and co-workers [21] reported that a dinuclear chromophore-catalyst dyad 28 showed photocatalytic oxidation of water with TON value (6 h) of 134 as irradiated by a blue (λmax = 472 nm) LED light source in the presence of sodium persulfate, which is much greater than a TON of only 6 for the uncoupled system. This group has also systematically studied photochemical water oxidation properties of a series of chromophore-catalyst dyads 29-35 [37].…”
Section: Electron Acceptormentioning
confidence: 99%
“…Although their catalytic activity is low, it represents a breakthrough in the area by opening new possibilities as photocatalysts for water oxidation. In all examples described, the activity of the dyad is higher than the two separate components, a phenomenon ascribed to fast intramolecular electron transfer kinetics that allows to reach the needed active higher oxidation states of the catalyst [13,14]. However, all the examples above are based on As drawn, this reaction takes place in 100 % atom economy and it generates a sulfoxide, which is a highly added value product, using water and sunlight.…”
Section: Light-driven Water Oxidationmentioning
confidence: 98%